María Gabriela Raviña : 17/12/1955 - 06/02/2008. - Callegari, Adriana B. (2008)
Fil: Callegari, Adriana B.. Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Arqueología; Argentina.